(untitled) (Revista Española de Fisiología, 1988)
The concentration of total lipids, free fatty acids and free carnitine in seven different regions of human ventricular myocardium has been studied.Statistically significant differences were found in the concentration of these compounds in the studied regions, with a similar behaviour for free carnitine and free fatty acids (their highest concentrations were found in the lower zones of the left ventricle).The results obtained support the theory of a different metabolic requirement in relation to the intensity of muscular contractile activity.